From Administrator to Instructional Leader: A Narrative Literature Review of the Evolution of the Principal's Role - Sandi; Dewi Cahyani; Moh. Ali (al-Afkar, Journal For Islamic Studies, 2026)
The role of the principal has fundamentally shifted from a traditional administrative function to a role as an instructional leader that emphasizes improving the quality of learning processes and outcomes. This article is a narrative literature review that examines the evolution of the principal's role in the 21st century with a focus on the context of Indonesian schools. This study integrates findings from empirical and conceptual literature from the past five years (2020–2025) to formulate a conceptual framework regarding the tasks, competencies, practices, barriers, and policy implications for school leadership transformation. The results indicate three main shifts: (1) an orientation from administrative management to instructional and visionary leadership; (2) the need for digital competency and change management in the face of Society 5.0 and the implementation of the Independent Curriculum; and (3) the need for policy support, ongoing training, and an outcome-based evaluation system. This article recommends that educational stakeholders in Indonesia design principal development programs that are contextual, sustainable, and focused on improving learning.